Designing and Determining Psychometric Properties of the Domestic Elder Abuse Questionnaire - Majid Heravi-Karimooi; Monireh Anoosheh; Mahshid Foroughan; Mohammad Taghi Sheykhi; Ebrahim Hajizadeh (University of Social Welfare & Rehabilitation Sciences, 2010)
Objectives: The purpose of this methodological study was to design and determine the psychometric properties of a new and specific questionnaire for assessing domestic elder abuse in the context of Iranian culture. Methods & Materials: This study was conducted in three phases. In the first phase, phenomenology was applied to explore the meaning of domestic elder abuse phenomenon. In the second phase, a questionnaire was compiled, using the results of the qualitative research implemented in the first phase, in conjunction with the inductions from the expert panel. In the third phase, the psychometric properties including face validity, content validity, construct validity, internal consistency, and test- retest reliability were measured. 325 elderly people who were selected randomly participated in the last stage. Results: The initial 78 item questionnaire designed using the results of first and second phases of study, reduced to 49 items in the process of determining the face and content validity. The result of exploratory factor analysis showed that this questionnaire contains 8 factors including care neglect, psychological abuse, physical abuse, financial abuse, curtailment of personal autonomy, abandonment, financial neglect and emotional neglect. These 8 factors explained nearly 79.93% of the variance. The results of known groups' comparisons showed that this questionnaire could successfully discriminate between subgroups of elderly people in the indexes of re-hospitalization and functional status. The internal consistency (Cronbach’s alpha) was 0.90–0.975. Test-retest reliability (ICC) of the questionnaire with interval time of two weeks was 0.98 (P<0.001). Conclusion: We concluded that the Domestic Elder Abuse questionnaire with 49 items appears to be a promising tool, providing reliable and valid data helping to detect abuse among elders in different settings such as clinical settings, homes and research environments by health care providers and researchers.